A comparison of gantry‐mounted x‐ray‐based real‐time target tracking methods. Issue 3 (13th February 2018) - Montanaro, Tim; Nguyen, Doan Trang; Keall, Paul J.; Booth, Jeremy; Caillet, Vincent; Eade, Thomas; Haddad, Carol; Shieh, Chun‐Chien
Abstract : Purpose: Most modern radiotherapy machines are built with a 2D kV imaging system. Combining this imaging system with a 2D‐3D inference method would allow for a ready‐made option for real‐time 3D tumor tracking. This work investigates and compares the accuracy of four existing 2D‐3D inference methods using both motion traces inferred from external surrogates and measured internally from implanted beacons. Method: Tumor motion data from 160 fractions (46 thoracic/abdominal patients) of Synchrony traces (inferred traces), and 28 fractions (7 lung patients) of Calypso traces (internal traces) from the LIGHT SABR trial (NCT02514512) were used in this study. The motion traces were used as the ground truth. The ground truth trajectories were used in silico to generate 2D positions projected on the kV detector. These 2D traces were then passed to the 2D‐3D inference methods: interdimensional correlation, Gaussian probability density function (PDF), arbitrary‐shape PDF, and the Kalman filter. The inferred 3D positions were compared with the ground truth to determine tracking errors. The relationships between tracking error and motion magnitude, interdimensional correlation, and breathing periodicity index (BPI) were also investigated. Results: Larger tracking errors were observed from the Calypso traces, with RMS and 95th percentile 3D errors of 0.84–1.25 mm and 1.72–2.64 mm, compared to 0.45–0.68 mm and 0.74–1.13 mm from the Synchrony traces. The Gaussian PDF method was found to be the most accurate, followed by the Kalman filter, the interdimensional correlation method, and the arbitrary‐shape PDF method. Tracking error was found to strongly and positively correlate with motion magnitude for both the Synchrony and Calypso traces and for all four methods. Interdimensional correlation and BPI were found to negatively correlate with tracking error only for the Synchrony traces. The Synchrony traces exhibited higher interdimensional correlation than the Calypso traces especially in the anterior‐posterior direction. Conclusion: Inferred traces often exhibit higher interdimensional correlation, which are not true representation of thoracic/abdominal motion and may underestimate kV‐based tracking errors. The use of internal traces acquired from systems such as Calypso is advised for future kV‐based tracking studies. The Gaussian PDF method is the most accurate 2D‐3D inference method for tracking thoracic/abdominal targets. Motion magnitude has significant impact on 2D‐3D inference error, and should be considered when estimating kV‐based tracking error.